Influence of fillets onto mechanical properties of octet-truss lattice structures - Doutre, Pierre-Thomas; Grandvallet, Christelle; Gobet, Léa; Vignat, Frédéric; Dendievel, Rémy (International journal of advanced manufacturing technology, 2024)
The development of additive manufacturing (AM) for the fabrication of metallic parts allows structures to be directly manufactured from 3D models. The electron beam melting (EBM) technology is an example of AM technologies that enable the manufacturing of new designs and sophisticated geometries. The process is particularly well suited for the fabrication of lattice structures. Octet-truss lattice structure has been a subject for research during the past 10 years. The potentials that it possesses attract enough interest for manufacturers to use it during the production of parts. Besides being lightweight, the structure could provide solid mechanical properties. However, researchers always encounter the same issue regarding this particular structure. During finite element analysis (FEA) simulation, stress concentration tends to appear at the strut intersection. This is due to the sharp edges that have very small surface area, thus provoking the presence of singularities. In this respect, the proposed solution is to integrate rounded joints or fillets at the strut intersection. However, adding fillet entails a mass increase of octet-truss structures. To avoid this mass increase related to these fillets, it is necessary to reduce the size of octet-truss struts. This research work studies the influence of fillets onto the mechanical properties of structures with identical mass. To do so, a set of 15 octet-truss structures are designed with various fillet sizes and strut sizes and compared. Whereas some of them have thick struts and small fillets, others have smaller struts and bigger fillets. The main technical issue in this study remains the design of fillets for octet-truss structures. These latter can indeed be created for up to 12 struts that converge to the same point. Once designed, these octet-truss structures are fabricated by EBM technology and undergo static compression testing. Mechanical properties of each structure are finally determined. Results show that for the same relative density, octet-truss with fillets degrades the mechanical characteristics of the whole structure. This study shows that the strength/mass ratio is better for a structure without fillets.